EIB Operations Inside the European Union 2019 - European Investment Bank (European Investment Bank, 2020)
Every year, the EIB takes a hard look at the work we do across Europe. We want to see if we are meeting goals for innovation, small businesses and the climate. We want to be sure that our projects are making a big difference in people's lives. One day our work might involve investments in better trains that encourage people to use fewer cars or new rockets that help Europe stay competitive in space. Another day, we might help the expansion of high-speed internet in people's homes or improve scientific research in a university. Take a peek inside this report to see more examples of how we improve lives.